Sunday
March 26, 2017

Post a New Question

Posted by on .

Solve the equation.

log 6.44 + 3 log x - log x^2 = log 6.44 + 3

  • Math - ,

    The same ambiguous question was posted here
    and I answered it as I understood it.

    You did not respond at the time

    http://www.jiskha.com/display.cgi?id=1271367239

  • Math - ,

    I just noticed you changed it slightly
    Now it becomes
    3 log x - log x^2 = 3
    log x^3 - log x^2 = 3
    log (x^4/x^2) = 3
    log x = 3
    x = 10^3 = 1000

  • Math - ,

    Thank you so much. I understand it now.

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question